Analysis of Management and Utilization of Non-Halal Funds - Andika Rusli; Sri Ayu Astuti AP; I Ketut Patra (Kontigensi : Jurnal Ilmiah Manajemen, 2020)
The purpose of this study is to find out how the practice of managing and utilizing non-halal funds at BAZNAS Palopo City for the last three years, namely 2018 to 2020, and its compliance with PSAK 109. The method used is descriptive qualitative with an inductive approach. This study found that BAZNAS has managed and utilized its non-halal funds properly and is by PSAK 109. However, its utilization from 2018 to 2020 has not been distributed because the receipts are only small; later, humans should not consume it if distributed. More widely used for roads, bridges, and latrines, including office building maintenance.